Penyuluhan terkait Bimbingan Karir bagi Mahasiswa Universitas Singaperbangsa Karawang guna Meningkatkan Kesiapan Memasuki Dunia Kerja - Nopiana, Medi; Manda, Gusganda Suria; Ariyani, Risma; Anggraini, Alvira; Rahma, Amelia (Jurnal Abdimas Perbanas, 2025)
The increasing demands of today's workforce recipients encourage efforts to enhance university student readiness in transitioning to the work atmosphere. To support these needs, the community service team held community service through career guidance activities for university students of Universitas Singaperbangsa Karawang. The method of implementing the activity employed counseling. The results of this activity provide benefits for university students, including obtaining new knowledge and raising insight concerning the work atmosphere, as well as strengthening university students' understanding of the sub-field of Human Resource Management. The community service team suggests that this activity can be held in the future by inviting different speakers and covering a wider range of participants.